Wireless Communication Networks and Internet of Things Select Proceedings of ICNETS2, Volume VI - Zungeru, Adamu Murtala; Subashini, S.; Vetrivelan, P. (Lecture Notes in Electrical Engineering, 2019)
This book is a collection of papers from international experts presented at International Conference on NextGen Electronic Technologies (ICNETS2-2016). ICNETS2 encompassed six symposia covering all aspects of electronics and communications domains, including relevant nano/micro materials and devices. Presenting recent research on wireless communication networks and Internet of Things, the book will prove useful to researchers, professionals and students working in the core areas of electronics and their applications, especially in signal processing, embedded systems and networking.